The Effect Of Combination Of Stocking Density And Food Types On Gonad Maturation And Egg Quality Of Hard Lipped Barb (Osteochilus hasselti CV) - Nul Khakim, Akhmad Lukman; Alawi, Hamdan; ', Sukendi (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The effect of combination of stocking density and food types on gonad maturity and egg quality of hard lipped barb (Osteochillus hasselti CV) was conducted from April to June 2015 at the Laboratory of Fish Hatchery and Breeding, Faculty of Fisheries and Marine Sciences University of Riau. The broodstocks were reared in the 300-L cages placed in 3x2x1 m concrete tank for 80 days rearing period. The treatments were stocking density 20 fish/cage fed on tubifex worm (SD-20-TB), SD 20 fed on pellet dry feed (PL); SD-20 fed on PL+Vit E; SD-30 TB; SD30 PL; SD30 PL+VitE; SD40, TB; SD40 PL and SD40 PL+VitE. Fish stocked at 20 fish fed on PL+VitE produced the best result in term on the number of Fish reached at mature stage (Maturity Stage IV), (50%), fecundity (360 eggs/g fish) , Gonado Somatic Index (GSI, 14.7%), egg diameter (0.94 mm) and percent egg maturity was 75%. Temperature range of 29-30 oC, pH 5-6, and dysolved oxygen of 2.43-3.18 mg/L. Key words : Oseochillus hasselti; stocking density; feed types, Vitamin E, gonad maturity, egg quality